2012
DOI: 10.1007/s10882-012-9285-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Adolescents with a Disability and Their Parents: The Mediating Role of Social Support and Resilience

Abstract: The aim of this study was to test whether the effect of the pile-up of demands associated with a disability on quality of One of the core notions in the systemic approach is that families form an interactive and interdependent system where what happens to one family member will also affect all the other members of the system (Goldenberg & Goldenberg, 2003;Turnbull & Turnbull, 2001). The disability of a child is such an event that will affect the whole family. Compared to families with typically developing chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 51 publications
2
58
0
9
Order By: Relevance
“…Families with a child with a disability often experience a strong bond and parentechild interactions. 12 Parents are often responsible for coordinating the care for a child living with a disability. 13 Social resources can help parents cope with the many challenges associated with caring for a child with a disability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Families with a child with a disability often experience a strong bond and parentechild interactions. 12 Parents are often responsible for coordinating the care for a child living with a disability. 13 Social resources can help parents cope with the many challenges associated with caring for a child with a disability.…”
mentioning
confidence: 99%
“…14 Adverse effects associated with caring for a child with a disability may include: high levels of stress, negative feelings toward parenting, less satisfaction with their marriage, financial and physical burden. 12,15 Without adequate support, families with a child with a disability may not be able to provide optimal support.…”
mentioning
confidence: 99%
“…Quality of life is a universal, multidimensional concept (Cummins, 1997;Schalock et al, 2002;Schalock & Felce, 2004) including a person's material well-being, health, productivity, intimacy, safety, community, and emotional well-being. In line with previous research within families with a disability (see Migerode, Buysse, Maes, & Brondeel, 2012c), family members' subjective reports about their satisfaction with each of these life-domains will be used as an index of their subjective quality of life.…”
Section: Intergenerational Influence and Quality Of Lifementioning
confidence: 99%
“…Alpha coefficients in this study ranged from to .84 to .90. The ComQol has been previously used in other studies with a similar sample of children with a disability (Migerode et al, 2012c).…”
Section: Quality Of Lifementioning
confidence: 99%
“…A vast numbers of studies has concluded that resilience is a protective factor against the development of psychiatric disorders, such as PTSD and depression [1]. Resilience has been shown to contribute to disaster victims' recovery, and has been generally positively related to people's mental health and quality of life [2].…”
Section: Introductionmentioning
confidence: 99%